Guía Didáctica del Sistema de Gestión Ambiental (ISO 14001: 2004) - Sistema de Gestión S&SO (OHSAS 18001: 2007), en la Fabricación de Bloque, a Base de Arcilla; en el Municipio de Susa (Cundinamarca) (2014)
The elaboration of this didactic guide of integrated systems of management ISO: 14001 and OHSAS: 18001. It is carried out after different visits investigating the processes in the manufacture of block. There is evidence of a lack of information regarding the subject of occupational safety and health and of the environment, with workers being affected as work accidents and occupational diseases increase. In addition, the inhabitants are being affected by the environmental impact emitted by block manufacturing and the lack of mitigation by employers. There is a need to provide the owners of block factories in the municipality of Susa with a didactic tool to the continuous improvement and generation of employment. To do this, it is clearly and generally described how to begin to address the implementation of the two systems and this is focused on raising the awareness of the owners of the factories, evidencing the risks to which the workers and inhabitants are exposed. of the owners of the block factories the commitment and the responsibility of adopting the present didactic guide, in the same way they will be made known, the integration of these two systems turning these into benefits.